AAV Vector-Mediated Antibody Delivery (A-MAD) in the Central Nervous System - Marino, M (2022)
In the last four decades, monoclonal antibodies and their derivatives have emerged as a powerful class of therapeutics, largely due to their exquisite targeting specificity. Several clinical areas, most notably oncology and autoimmune disorders, have seen the successful introduction of monoclonal-based therapeutics. However, their adoption for treatment of Central Nervous System diseases has been comparatively slow, largely due to issues of efficient delivery resulting from limited permeability of the Blood Brain Barrier. Nevertheless, CNS diseases are becoming increasingly prevalent as societies age, accounting for ~6.5 million fatalities worldwide per year. Therefore, harnessing the full therapeutic potential of monoclonal antibodies (and their derivatives) in this clinical area has become a priority. Adeno-associated virus-based vectors (AAVs) are a potential solution to this problem. Preclinical studies have shown that AAV vector-mediated antibody delivery provides protection against a broad range of peripheral diseases, such as the human immunodeficiency virus (HIV), influenza and malaria. The parallel identification and optimization of AAV vector platforms which cross the Blood Brain Barrier with high efficiency, widely transducing the Central Nervous System and allowing high levels of local transgene production, has now opened a number of interesting scenarios for the development of AAV vector-mediated antibody delivery strategies to target Central Nervous System proteinopathies.